IDENTIFIKASI CULTURAL AWARENESS DALAM KONSELING LINTAS BUDAYA DENGAN BERBASIS INCLUSIVE CULTURAL EMPATHY (ICE) BAGI SISWA/I DI NUSA TENGGARA TIMUR - Triati Lestari Salau; Katharina E. P. Korohama (Bethel Press, 2023)
Cultural Awareness not only reduces the ignorance and fear that counselors may have of counselees as another cultural group but encourages a new generation of counselors with the potential for Inclusive Cultural Empathy to produce an inclusive counseling approach. The purpose of this research is to identify the factual conditions of Cultural Awereness and to analyze the description of the factual models of cross-cultural counseling in schools. The method used is Mix Methods Research. Quantitative data shows that 60% of counseling guidance teachers have low Cultural Awereness, 25.7% are in the medium and 14.3% are in the high category. The factual model of cross-cultural counseling carried out in schools displays an element of acceptance that has not yet reached a cultural emotional connection so that cultural empathy is not achieved. As a result, there are negative feelings within the counselee due to cultural bias by the Guidance and Counseling Teacher.